Effects of Slender Carpetweed (Mollugo oppositifolia) Extract on Intestinal Worms of Native Chicken (Gallus gallus domesticus) - Latoza, Franciss John; Estudillo, Sinamar E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Poultry is the fastest growing component and one of the most efficient and effective means of food supply to the society in the form of meat and egg. Parasitic infections lead to low productivity and increased mortality in poultry. A total of forty-five (45) apparently healthy Philippine native chickens, regardless of sex and weight, ranging from 4-6 months of age, were randomly distributed in five (5) treatments. Each treatment was replicated thrice with three (3) birds per replication following the Completely Randomized Design (CRD). Simple Test Tube Flotation was used to establish which parasite groups are present in the fecal samples. The McMaster technique was also used as a counting chamber which enables a known volume (2 x 0.15 ml) of fecal suspension to be examined microscopically. The number of eggs per gram was calculated by counting the number of eggs within the grid of each chamber which gave the data on eggs per gram (EPG) of feces. The results revealed in T4 (1ml) slender carpet weed extract and T5 (1.5ml) have anthelmintic potentials when used in native chickens. Thus, slender carpet weed extract is an effective deworming agent. Slender carpet weed extract is effective in lowering the egg per gram of intestinal parasites found in native chickens. The optimum volume to ensure effectivity is 1.5 ml which revealed the strongest effect in reducing intestinal worms.